Commercial law - Baskind, Eric; Osborne, Greg; Roach, Lee (College teacher) (Oxford (UK): Oxford University Press, 2022)
This text is written and designed to help you succeed. Accurate and reliable, 'Concentrate' guides help focus your revision and maximise your exam performance. Each guide includes revision tips, advice on how to achieve extra marks, and a thorough and focused breakdown of the key topics and cases.
Includes bibliographical references and index.
Keywords: Commercial law -- Great Britain; Commercial law; Laws of specific jurisdictions & specific areas of law; Law; Great Britain